Exploring the reproductive health needs of men in the preconception period: A qualitative study - Zeinab Rabiei; Mohammad Shariati; Naser Mogharabian; Rahim Tahmasebi; Ashraf Ghiasi; Zahra Motaghi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Male reproductive health is a necessary pillar of childbearing. If a reproductive health assessment is conducted in the preconception period, the chance of a healthy pregnancy can increase. This qualitative study aimed to explore men's reproductive health needs before conception in Iran. MATERIALS AND METHODS: This research was a qualitative study conducted in Bushehr city, Iran to explore men's reproductive health needs from April 2021 to November 2021. 30 semistructured interviews were conducted with married men, women, healthcare providers, and specialists individually in the health centers. The sampling method used in this study was purpose-based with maximum variety. All interviews were digitally recorded and transcribed verbatim in Persian and analyzed using directional content analysis. MAXQDA software version 12 was used to facilitate data analysis. RESULTS: From the data analysis, 2 themes, 15 categories, and 38 subcategories emerged. The themes included evaluation and health promotion recommendations. It consisted of 10 categories: reproductive life plan evaluation, medical history evaluation, family and genetic history evaluation, social history evaluation, sexual health evaluation, medication evaluation, laboratory evaluation, physical examination, lifestyle evaluation, and mental health evaluation. Health promotion recommendations included five categories: nutritional recommendations, stress management, avoiding harmful behaviors, protective measures against harmful exposure, and need for education. CONCLUSIONS: Our results showed that men need a comprehensive evaluation of reproductive health and recommendations to improve their health in the preconception period. Our study findings can inform healthcare providers to increase men's participation in reproductive health.